PENGAWASAN PEMERINTAH KOTA DUMAI TERHADAP USAHA KARAOKE TAHUN 2013-2014 - Ahmad Fauzan; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Karaoke businesses in Kota Dumai growing very rapidly. Karaoke is a business that provides space, equipment and facilities for singing to the accompaniment of recorded music as well as provide restaurant or restaurant. There are deviations resulting from the presence of the karaoke business. So the karaoke business supervision is essential to prevent penympangan-deviations.The method used in this study is qualitative methods of data processed not in the form of numbers, but in the form of an explanation that describes the shape of the state, process, certain events. Data collection techniques using interview techniques, documentation and observation.Results of this study illustrate that the implementation of the supervision of the karaoke business in Kota Dumai still not performing well, ranging from preventive and repressive control, and no firmness in imposing sanctions. This is evidenced by the presence of karaoke places that do not have a license, which provides a moral violation female commercial sex workers, selling illegal liquor-liquor, selling drugs, breaking the operating hours and other things that are contrary to Dumai Mayor Regulation No. 21 Year 2013 About Procedures and Procedures for Tourism Business License.Keywords : Monitoring , Preventive , Repressive